Phoneme dependence of horizontal asymmetries in voice directivity - Pörschmann, Christoph; Arend, Johannes M. (JASA express letters, 2024)
Human voice directivity shows horizontal asymmetries caused by the shape of the lips or the position of the tooth and tongue during vocalization. This study presents and analyzes the asymmetries of voice directivity datasets of 23 different phonemes. The asymmetries were determined from datasets obtained in previous measurements with 13 subjects in a surrounding spherical microphone array. The results show that asymmetries are inherent to human voice production and that they differ between the phoneme groups with the strongest effect on the [s], the [l], and the nasals [m], [n], and [ŋ]. The least asymmetries were found for the plosives.